Serum concentration of cobalt, molybdenum and zinc in aerobic, anaerobic and aerobic-anaerobic sportsmen - Maynar, M.; Llerena, F.; Grijota, F. J.; Perez-Quintero, M.; Bartolomé, I.; Alves, J.; Robles, M. C.; Muñoz, D. (Journal of the International Society of Sports Nutrition, 2018)
Background: The aim of the present study was to determine changes in the serum concentrations of trace elements Cobalt (Co), Molybdenum (Mo) and Zinc (Zn) among high-level sportsmen. Methods: Eighty professional athletes of different metabolic modalities (aerobic, anaerobic and aerobic-anaerobic), were recruited before the beginning of their training seasons. Thirty-one sedentary participants of the same geographic area constituted the control group. Co, Mo and Zn analysis was performed by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Results: Serum concentration of Mo (p < 0.001) was higher among sportsmen compared to the control group values. Separated by modalities, the concentrations of Co in the aerobic-anaerobic athletes were lower (p < 0.01) than in the control group as well as than in the other athletes. The highest Mo concentration was found in anaerobic sportsmen (p < 0.001), followed by aerobic-anaerobic (p < 0.001) being both statistically higher in comparison with the control group. In relation to Zn, it was observed that aerobic-anaerobic (p < 0.001) and anaerobic (p < 0.001) sportsmen showed higher concentrations than the control participants. However, aerobic sportsmen showed lower concentrations (p < 0.01) than controls. Conclusion: This data manifest that long-term, daily physical training may induce variations in serum concentrations of several essential elements among sportsmen in comparison to untrained men and that these changes seems to be related to the sports modality practiced.